DEMOGRAPHIC AND ICTIOLOGICAL ANALYSIS OF THE CAPTURES CARRIED OUT WITH A FIXED TRAP NETWORK IN THE GANDOCA LAGOON, LIMÓN, COSTA RICA - Benavides-Morera, Rosario (2010)
An ichthyological study of the fishing catch in a fixed trap net along with hydrographic sampling of the hydrological properties in Gandoca Lagoon, Limón, was carried out between April 2006 and July 2007. Thirteen species belonging to 10 families were identified. Ninty-eight percent of the captures belong to four species of commercial value: Centropomus pectinatus (77%), Eucinostomus gula (9%), Caranx latus (7%) and Stellifer colonensis (5%). C. pectinatus was present in all captures. For C. pectinatus (snook), the relationship between total length and weight was adjusted potentially through the equation Pt= 0.004Lt3.1848. The size of first maturity of snooks was 30 cm. The annual cycle of surface termohaline properties shows the maximum temperature in September (32°C) and the minimum during December (25.5°C). The Lagoon exhibits maximum salinities in October (21) and minimum in July and December (1). Between September and November the influence of the tidal wave extends to the middle of the lagoon with salinities of 20, while in the inner part it does not exceed 5. The highest values in oxygen content were observed between September and November, when the contribution of fresh water runoff is minimal. The space-time characteristics of the salinity field have a direct influence on the composition and distribution of the icthyofauna that inhabits the Lagoon.